A comparative study of Al2O3 coated LHR engine characteristic using rice bran and mahua methyl ester as a fuel. (1st January 2012) - Mohamed Musthafa, M.; Sivapirakasam, S.P.; Udayakumar, M.
In this study, for the first time, a nano material of Al2 O3 was used as ceramic layer in low heat rejection engine concepts. The coating was carried out by plasma spray method on the combustion chamber surfaces (cylinder head, cylinder liner, valves and crown surfaces) of the DI diesel engine. A comparative evaluation of Al2 O3 coated engine was carried out between two types of biodiesel (methyl ester of rice bran and mahua oil) and diesel. Experiments were conducted on single cylinder, four strokes, water cooled and direct injection diesel engine. The test run was also repeated for uncoated engine and compared. The results indicated that, an increase in engine power (6.3–11.4%) and decrease in specific fuel consumption (0.8–10.9%), as well as significant improvements in exhaust gas emissions (except NOx) and smoke opacity (19.6–28.9%) were observed in Al2 O3 coated engine compared with that of the uncoated engine.